A further refinement of procedures addressing food selectivity. (31st July 2019) - Russo, Samantha R.; Croner, Jennifer; Smith, Samantha; Chirinos, Meaghan; Weiss, Mary Jane
Abstract : Individuals with autism and/or developmental disabilities are more likely than their typically developing peers to be food selective. Evidence‐based treatment packages for food refusal and selectivity include the use of reinforcement, escape extinction, and manipulation of antecedent events . In the current study, the variety of foods consumed by two adolescent males with food selectivity were systematically increased to include a variety of foods across all of the food groups. A changing criterion design was used to systematically increase the expectation of the amount and variety of foods that were consumed.